Бібліотека Митрополита Анатолія (Дублянського): тематичний склад та сучасний стан - Фульмес, В. (Краєзнавство, 2018)
У статті розглянуто історію передачі приватної бібліотеки відомого ієрарха Української Автокефальної Православної Церкви в діаспорі митрополита Західноєвропейського і Паризького Анатолія (Дублянського) до Волинської духовної семінарії. Подані відомості про тематичний склад книгозбірні та сучасний стан її зберігання. Metropolitan of Western European and Parisian Anatoliy (Dublyansky) is an outstanding hierarch of
the Ukrainian Autocephalous Orthodox Church in the diaspora, a native of Volyn, who has left a remarkable
mark in the development of the culture of his native land and Ukrainian Autocephalous Orthodox Church in
Germany. Emigrated to Germany in 1944, he took an active part in the establishment of church-religious life.
During his 50 years of emigration, Bishop Anatoliy collected a large private library, which, after declaration
of Ukraine’s independence and in view of problem with health, he decided to transfer it to the Motherland.
This article shows the history of the transferring of the private library of the Metropolitan of Western European
and Parisian Anatoliy (Dublyansky) to Ukraine, namely, to the Volyn Theological Seminary. Thanks to the «List
of books and brochures of church-religious nature ...», authored by Bishop Anatoliy himself, it is possible to
follow the content of the church-religious library of Metropolitan. The article presents some inscripts from
books that show how a particular book has fallen into the private library of the Metropolitan. Also indicated
where the valuable acquisition of Metropolitan Anatoly (Dublyansky) is kept. В статье рассмотрена история передачи частной библиотеки известного иерарха Украинской
Автокефальной Православной Церкви в диаспоре митрополита Западноевропейского и Парижского
Анатолия (Дублянского) в Волынскую духовную семинарию. Представленные сведения о тематическом
составе библиотеки и современное состояние ее хранения.